1989
DOI: 10.7326/0003-4819-110-3-183
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dextran Sulfate (UAOO1) in the Treatment of the Acquired Immunodeficiency Syndrome (AIDS) and AIDS-Related Complex

Abstract: Oral dextran sulfate appears to be well tolerated. No evidence of systemic absorption of the parent compound is available. However, in view of the promising in vitro effects and acceptable toxicity, oral dextran sulfate as a potential antiretroviral agent continues to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(44 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…To determine whether mCDS acts on the viral envelope glycoprotein or cell CD4 receptors, the Sulphated polysaccharides such as DS have been reported to inhibit selectively HIV-1 and HIV-2 activity in vitro. However, there are no reports showing the in vivo effectiveness of these compounds in humans (Abrams et al, 1989). DS administered orally to humans is virtually unabsorbed (Lorentsen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether mCDS acts on the viral envelope glycoprotein or cell CD4 receptors, the Sulphated polysaccharides such as DS have been reported to inhibit selectively HIV-1 and HIV-2 activity in vitro. However, there are no reports showing the in vivo effectiveness of these compounds in humans (Abrams et al, 1989). DS administered orally to humans is virtually unabsorbed (Lorentsen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Serum drug concentrations achieved by these sulfated polymers were highly dependent on the route of administration. Clinical trials of oral OS (Abrams et al, 1989) and PS (Peters et al, 1989) were terminated soon after the drug was shown to be poorly absorbed (bioavailability < 1%) (Lorentsen et al, 1989). No significant changes in surrogate markers (p24) or clinical endpoints (CD4), suggesting anti-HIV activity, were recorded from those trials.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Aurintricarboxylic acid predominantly interacts with the CD4 receptor (Schols et al, 1989), whereas dextran sulphate has a shielding effect on the viral gp120 protein (Schols et al, 1990). Despite the low clinical activity of dextran sulphate when orally administered (Abrams et al, 1989), this polyanionic molecule is the prototype for other anionic derivatives that can block viral replication by inhibiting viral binding. Inhibition of viral capsid assembly might be an alternative mechanism, as was shown recently for a sulphonic acid derivative (Teschke et al, 1993).…”
Section: Introductionmentioning
confidence: 99%